Relationships between biotic indices, multiple stressors and natural variability in New Zealand estuaries. (February 2018) - Berthelsen, A.; Atalah, J.; Clark, D.; Goodwin, E.; Patterson, M.; Sinner, J.
Highlights: A long-term nationwide estuary dataset was compiled to test index performance. A modified version of AMBI had the most variation explained by stressors. The Traits Based Index showed significant effects from all stressors tested. Natural and unexplained variation were relatively high for all indices. We suggest the use of more than one index i.e. a weight of evidence approach. Abstract: In response to the need to assess the ecological quality or health of marine benthic habitats, there has been a proliferation of biotic indices based on soft sediment macrofaunal communities. While shown to be useful in areas where they have been developed, some indices may not be readily transferrable to other regions due to differences in species ecology or composition, stressor type or magnitude, and natural variability. Using a national New Zealand dataset compiled from estuary monitoring data for 2001–2016, we used linear mixed models to determine the effect of multiple stressors (sediment mud content, metals and total phosphorus) and natural variability (associated with space, estuary type and time) on nine indices developed in New Zealand and overseas. The Richness-Integrated AZTI Marine Biotic Index (RI-AMBI), a modification of a popular overseas biotic index, had the most variation explained by stressors overall (marginal pseudo-R 2  = 0.22 compared to ≤0.15 for all other indices). This variation was primarily explained by a single stressor, sediment mud content, which is the dominant stressor in New Zealand estuaries. However, although the overall variation explained by stressors was lower for all other indices, multiple, rather than single, stressors had significant effects on some indices. For example all three stressors had a significant effect on the Traits Based Index, and the variation explained by metals was highest for this index. Relatively high amounts of natural and unexplained variation for all indices suggested that further understanding is required before operational implementation of indices at a national scale. Thus, the use of more than one index, i.e. a weight of evidence approach, is suggested to minimise uncertainty related to inaccuracy and misclassification of ecological health in New Zealand estuaries.